2012
DOI: 10.1182/blood-2011-06-364273
|View full text |Cite
|
Sign up to set email alerts
|

Lymph node B lymphocyte trafficking is constrained by anatomy and highly dependent upon chemoattractant desensitization

Abstract: IntroductionLymphocyte homeostasis in resting lymph nodes (LNs) is maintained by the entry of circulating lymphocytes through high endothelial venules (HEVs) and exit through lymphatic vessels. CD62L on lymphocytes interacts with ligands on HEVs in LNs to initiate the rolling of lymphocytes along the luminal surface. 1,2 As the lymphocytes roll, cognate G-protein coupled receptors (GPCRs) engage homeostatic chemokines present on the luminal surface of HEVs triggering lymphocyte adhesion and the exploration for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
61
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 58 publications
(68 citation statements)
references
References 42 publications
6
61
0
1
Order By: Relevance
“…This is similar to observations made by Park and colleagues. 5 This may be due to one or several of the following scenarios: subsets of stromal cells in the T-cell area express CXCL13, 38 which may present low levels of CXCL13 in the T-cell area, thereby disrupting a chemotactic gradient. However, in immunofluorescent sections, virtually all detectable CXCL13 is found in B-cell follicles.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This is similar to observations made by Park and colleagues. 5 This may be due to one or several of the following scenarios: subsets of stromal cells in the T-cell area express CXCL13, 38 which may present low levels of CXCL13 in the T-cell area, thereby disrupting a chemotactic gradient. However, in immunofluorescent sections, virtually all detectable CXCL13 is found in B-cell follicles.…”
Section: Discussionmentioning
confidence: 99%
“…The labeling for HEV allowed us to discard tracks in the perivascular space where migration is lower than in the parenchyma. 3,5 While the track distribution analysis confirmed that CXCR5 was required for efficient entry into the follicular microenvironment, CXCR5…”
Section: Cxcr5 Controls B-cell Follicle Entry and Migration Speed In mentioning
confidence: 99%
See 3 more Smart Citations